2017
DOI: 10.1021/acsami.7b07092
|View full text |Cite
|
Sign up to set email alerts
|

Cu(In,Ga)Se2 Solar Cells with Amorphous In2O3-Based Front Contact Layers

Abstract: Amorphous (a-) InO-based front contact layers composed of transparent conducting oxide (TCO) and transparent oxide semiconductor (TOS) layers were proved to be effective in enhancing the short-circuit current density (J) of Cu(In,Ga)Se (CIGS) solar cells with a glass/Mo/CIGS/CdS/TOS/TCO structure, while maintaining high fill factor (FF) and open-circuit voltage (V). An n-type a-In-Ga-Zn-O layer was introduced between the CdS and TCO layers. Unlike unintentionally doped ZnO broadly used as TOS layers in CIGS so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Furthermore, the electron affinities and band gaps of amorphous TOS films can be controlled by choosing appropriate posttransition metals and compositions . Therefore, when incorporated in the front contact layers, In 2 O 3 ‐based materials can potentially generate higher conversion efficiency than ZnO‐based materials, and we demonstrate this concept with a ‐In‐Ga‐Zn‐O ( a ‐IGZO)/ a ‐In 2 O 3 :H front contact layers . Furthermore, several experimental studies revealed that In 2 O 3 ‐based TCOs reduced the electrical loss caused by series resistance and optical loss because of free carrier absorption within the TCO layer while improving the stability of solar cells and mini‐modules.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Furthermore, the electron affinities and band gaps of amorphous TOS films can be controlled by choosing appropriate posttransition metals and compositions . Therefore, when incorporated in the front contact layers, In 2 O 3 ‐based materials can potentially generate higher conversion efficiency than ZnO‐based materials, and we demonstrate this concept with a ‐In‐Ga‐Zn‐O ( a ‐IGZO)/ a ‐In 2 O 3 :H front contact layers . Furthermore, several experimental studies revealed that In 2 O 3 ‐based TCOs reduced the electrical loss caused by series resistance and optical loss because of free carrier absorption within the TCO layer while improving the stability of solar cells and mini‐modules.…”
Section: Introductionmentioning
confidence: 83%
“…A 50‐nm‐thick a ‐IGZO layer was deposited with no intentional substrate heating via rf magnetron sputtering deposition using an In‐Ga‐Zn‐O (In:Zn:Ga = 1:1:1) ceramic target with an O 2 /(Ar + O 2 ) flow ratio of 0.08%. In 2 O 3 :H films with thicknesses of 50, 70, and 150 nm were deposited with no intentional substrate heating via in‐line reactive plasma deposition using In 2 O 3 ceramic tablets and Ar, O 2 , and H 2 O gases at a total pressure of ca. 0.4 Pa and an H 2 O partial pressure of ca.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations